Your road map for success - Maxwell, John C.; Baz, Saeid Faris = (3HGR(B, (3SYjO aGQS s (Jordan Jabal Amman Publishers, 2009)
(3JMOjO fLGM egeI UYHI(B. (3eYXe GdfGS jSGhhf Hjfg hHjf GdKQhI hGdSdWI, hGdSYGOI(B. (3heY Pdc, aEf GdfLGM GdMbjbj djS TjA JMUd Ydjg Ch JMbjbg(B. (3HOdG ef Pdc, EfgG QMdI cfJ JCNP MjGJc cdgG WhjdI(B. (3HCSdhH eeJY hGVMI, Lhf eGcShjd JTGQc QDi aQjOI Mhd eG jYfjg Cf Jchf fGLMs
Includes bibliographical references and index.
In Arabic
Keywords: Success -- Psychological aspects